2/3(6x+9)-3x=-15

Simple and best practice solution for 2/3(6x+9)-3x=-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/3(6x+9)-3x=-15 equation:



2/3(6x+9)-3x=-15
We move all terms to the left:
2/3(6x+9)-3x-(-15)=0
Domain of the equation: 3(6x+9)!=0
x∈R
We add all the numbers together, and all the variables
-3x+2/3(6x+9)+15=0
We multiply all the terms by the denominator
-3x*3(6x+9)+15*3(6x+9)+2=0
Wy multiply elements
-9x^2(6+45x(6+2=0

See similar equations:

| x-259=78 | | 7/10m=-10 | | -3(-6+8x)-7x=-230 | | 3x-1-4x+7=-4 | | 0.8x-2.5=1.3x+2.8 | | 38=1x-5 | | -19x-1=12x-34 | | -8p=-8(p+1) | | -3(3x+7)=-9x+21 | | 2w-27=5ww=1/2 | | -3x+1=-3x-3 | | 11=k-4/5 | | -18-16n=-17n | | 25-(3x+5)=3x+16 | | (25)3x-2=425 | | 8=(-7n+5) | | 168=-6(6b+8) | | 5+x+23=53 | | 19t+2=–17 | | -1/2w-2/5=1/5w | | 11.74-8d=-2.5+6.6d-15.4d | | 2x^2=3X^2 | | 61+14x+8=27x+4 | | -4x-13=-4x+13 | | -88=8(1+2x) | | 9x-6=6x+8 | | -3v+4v=-2 | | -4-2x=x+2 | | -14.9j-19.2=-5.3j | | 4+6x=4x+22 | | ∣2x−6∣=4x | | -50x-24x=80+70 |

Equations solver categories